منهج مادة التربية الفنية في مرحلة التعليم الابتدائي ( الأساسي) بين الواقع والطموح - ا.م. غسان كاظم جبر; ا.م.د .امجد عبد الرزاق حبيب ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2019)
The practical activities contribute to developing creative and innovation skills to primary school students. In addition, it contributes to boosting social and educational practical Valuable. One of these activates is including the Art subjects to other school subjects, Art, unfortunately, is not an active subject in our primary school, hence, the current research aims to study the factors that obstacle the including if this vital subjects and submit an educational integrated course that depends on the integrity between the Art and the reading and mathematics subjects, it is an imagine suggestion to activate the activities of these subjects.